2001
DOI: 10.1177/036215370103100303
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Communication Skills Training on Ego States and Problem Solving

Abstract: This article describes an experimental study carried out to test the effectiveness of a communication skills program on transactional analysis ego states and the problem solving scores of prospective teachers. The experimental group participated in training, whereas the control group had no training. The Adjective Check List and Problem Solving Inventory were applied to both the experimental and control groups before and after treatment. Analysis of covariance test results showed that Critical Parent, Nurturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Nor was the common effect of the method implemented and gender found to have a significant effect on the students' problem-solving skills. These results are in line with the results of similar studies (Basmacı, 1998;Çam, 1996;Gholami et al, 2019;Görmez, 1998;Güven and Akyüz, 2001;Özdemir et al, 2016;Özkütük et al, 2003;Saracaloğlu et al, 2009;Serin, 2001;Syaiful et al, 2019). However, there are some studies Science Education International 31(4), 400-409 https://doi.org/10.33828/sei.v31.i4.9…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 88%
“…Nor was the common effect of the method implemented and gender found to have a significant effect on the students' problem-solving skills. These results are in line with the results of similar studies (Basmacı, 1998;Çam, 1996;Gholami et al, 2019;Görmez, 1998;Güven and Akyüz, 2001;Özdemir et al, 2016;Özkütük et al, 2003;Saracaloğlu et al, 2009;Serin, 2001;Syaiful et al, 2019). However, there are some studies Science Education International 31(4), 400-409 https://doi.org/10.33828/sei.v31.i4.9…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 88%
“…Even though scores were found slightly in favor of female gifted students in confidence dimension and total problem-solving skills, this result cannot be considered as an important superiority. When glancing to the previous studies results, many of them were failed to find a difference of problemsolving skills according to gender in primary education level (Terzi Işık, 2000;Şahin, 2000), high school level (Saygılı, 2000), and college level (Basmacı, 1998;Çam, 1997Çam, , Taylan, 1990. However, few studies reported that female performed better at problem-solving skills than males (Katkat, 2001;Ülger, 2003).…”
Section: Resultsmentioning
confidence: 76%
“…Scrutinizing the literature, it can be seen that there are quite a lot of studies that address Transactional Analysis (TA) and communication skills together (Akkoyun,1993;Alisinanoğlu & Köksal, 2000;Çam, 1999;Dökmen, 1996;Zengin, 2019). However, no experimental studies about the effect of Transactional Analysis training on communication skills have been discovered.…”
Section: Introductionmentioning
confidence: 99%